The Effect Of Dividend,Leverage, And Profitability Policies On Company Value With Capital Structure Moderation In The Mining Sector - Olivvia Anastasya; Lestari Wuryanti; Hiro Sejati (Asia Pacific Journal of Business Economics and Technology, 2026)
This study aims to examine and analyze the effect of dividend policy, leverage, and profitability on firm value, with capital structure as a moderating variable in the mining sector. The research was conducted on nine mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period using secondary data collection. A total of 27 observations were obtained over three years through purposive sampling. The research method employed a quantitative approach using panel data regression analysis and Moderated Regression Analysis (MRA) through EViews software. The results indicate that partially, dividend policy has a significant effect on firm value. In contrast, leverage and profitability were found to have no significant effect on firm value in the mining sector during the observation period. Simultaneously, the three independent variables have a significant effect on firm value. The moderation test results show that capital structure is not able to moderate the relationship between dividend policy, leverage, and profitability and firm value.